Influence of preceding length of anticoagulant treatment and initial presentation of venous thromboembolism on risk of recurrence after stopping treatment: analysis of individual participants' data from seven trials. (24th May 2011) - Boutitie, Florent; Pinede, Laurent; Schulman, Sam; Agnelli, Giancarlo; Raskob, Gary; Julian, Jim; Hirsh, Jack; Kearon, Clive
Abstract : Objective To determine how length of anticoagulation and clinical presentation of venous thromboembolism influence the risk of recurrence after anticoagulant treatment is stopped and to identify the shortest length of anticoagulation that reduces the risk of recurrence to its lowest level. Design Pooled analysis of individual participants' data from seven randomised trials. Setting Outpatient anticoagulant clinics in academic centres. Population 2925 men or women with a first venous thromboembolism who did not have cancer and received different durations of anticoagulant treatment. Main outcome measure First recurrent venous thromboembolism after stopping anticoagulant treatment during up to 24 months of follow-up. Results Recurrence was lower after isolated distal deep vein thrombosis than after proximal deep vein thrombosis (hazard ratio 0.49, 95% confidence interval 0.34 to 0.71), similar after pulmonary embolism and proximal deep vein thrombosis (1.19, 0.87 to 1.63), and lower after thrombosis provoked by a temporary risk factor than after unprovoked thrombosis (0.55, 0.41 to 0.74). Recurrence was higher if anticoagulation was stopped at 1.0 or 1.5 months compared with at 3 months or later (hazard ratio 1.52, 1.14 to 2.02) and similar if treatment was stopped at 3 months compared with at 6 months or later (1.19, 0.86 to 1.65). High rates of recurrence associated with shorter durations of anticoagulation were confined to the first 6 months after stopping treatment. Conclusion Three months of treatment achieves a similar risk of recurrent venous thromboembolism after stopping anticoagulation to a longer course of treatment. Unprovoked proximal deep vein thrombosis and pulmonary embolism have a high risk of recurrence whenever treatment is stopped.